Mild Effect of Nalmefene on Alcoholic Cue-Induced Response Invigoration in Alcohol Use Disorder Without Accompanying Changes in Electrophysiological Signatures of Early Visual Processing and Executive Control - Gál, Bernadett I.; Kilencz, Tünde; Albert, Anita; Demeter, Ildikó; Hegedűs, Klára Mária; Janka, Zoltán; Csifcsák, Gábor; Álmos, Péter Z. (Frontiers in Pharmacology, 2019)
Nalmefene is approved for as-needed pharmacological treatment in alcohol used disorder (AUD) by the European Medicines Agency (EMA). While the cellular effects of nalmefene have been thoroughly investigated, data is very limited on how this agent influences neural signals associated with inhibitory control and the visual analysis of environmental cues. This double-blind crossover study assessed the behavioral and neural effects of acute nalmefene administration in patients diagnosed with AUD. In Experiment 1, we validated our experimental paradigm (electroencephalography combined with a modified Go/NoGo task using images of alcoholic and non-alcoholic drinks as prime stimuli) in twenty healthy adults to ensure that our protocol is suitable for assessing the behavioral and neural aspects of executive control. In Experiment 2, we recruited 19 patients with AUD and in a double-blind crossover design, we investigated the effects of nalmefene vs. placebo on task performance (response accuracy, the sensitivity index and reaction times), visual responses to appetitive cues (occipital P1, N1 and P2 components) and electrophysiological markers of conflict detection and response inhibition (frontal N2 and P3 waveforms). Under placebo, patients produced faster reaction times to alcohol-primed Go stimuli, an effect that was weak despite being statistically significant. However, the effect of alcoholic cues on the speed of response initiation disappeared after receiving nalmefene. We found no placebo vs. nalmefene difference regarding our patients’ ability to accurately inhibit responses to NoGo stimuli or for occipital and frontal event-related potentials. Our results suggest that nalmefene might be potent in reducing the vigor to act upon alcoholic cues in AUD patients, but this effect is most probably mediated via subcortical (rather than cortical) neural circuits.